Safety evaluation of the food enzyme glucan 1,4‐α‐maltohydrolase from the genetically modified Bacillus subtilis strain BABSC - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme glucan 1,4‐α‐maltohydrolase (4‐α‐d‐glucan α‐maltohydrolase, EC 3.2.1.133) is produced with the genetically modified Bacillus subtilis strain BABSC by Advanced Enzyme Technologies Ltd. The requirements for the qualified presumption of safety (QPS) approach have not been met. The food enzyme is free from viable cells of the production organism and its DNA. It is intended to be used in baking processes and starch processing for the production of glucose syrups and other starch hydrolysates. Since residual amounts of total organic solids (TOS) are removed, dietary exposure was not calculated for starch processing for the production of glucose syrups and other starch hydrolysates. For baking processes, the dietary exposure was estimated to be up to 0.101 mg TOS/kg body weight per day in European populations. No toxicological studies were provided by the applicant. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and one match with a respiratory allergen was found. The Panel considered that the risk of allergic reactions by dietary exposure cannot be excluded, but the likelihood is low. In the absence of appropriate data to fully characterise the production strain, the Panel was unable to conclude on the safety of the food enzyme under the intended conditions of use.